2019
DOI: 10.1007/s11661-019-05548-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Dwell-Fatigue Crack Propagation Behavior of a High-Strength Ni-Base Superalloy Manufactured by Selective Laser Melting

Abstract: This study focuses on the dwell-fatigue crack propagation behavior of IN718 manufactured via selective laser melting (SLM). The dwell-fatigue test condition is 823 K (550 $$^{\circ }$$∘C) with a long 2160-s dwell-holding period. Effects of heat treatment and loading direction on dwell-fatigue crack propagation rates are studied. A grain boundary $$\delta $$δ precipitate seems to be slightly beneficial to the dwell-fatigue cracking resistance of SLM IN718. A comparison has been made between SLM IN718 and forged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Crack propagation of AM materials has previously been studied in e.g. Saarimäki et al [56], Deng et al [12], where out-of-plane crack propagation was observed at high temperatures. This, if also present for the considered material in this work, in combination with inelastic deformations where linear elastic fracture mechanics is invalid, can be a real challenge, but might be of relevance for future studies in this area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crack propagation of AM materials has previously been studied in e.g. Saarimäki et al [56], Deng et al [12], where out-of-plane crack propagation was observed at high temperatures. This, if also present for the considered material in this work, in combination with inelastic deformations where linear elastic fracture mechanics is invalid, can be a real challenge, but might be of relevance for future studies in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [8], Blinn et al [9] and Yadollahi et al [10], nickel-based superalloy Inconel 625, 718 and 939, cf. Gonzalez et al [11], Deng et al [12] and Kanagarajah et al [13], as CHAPTER 2. ADDITIVE MANUFACTURING well as Haynes 230, cf.…”
Section: Selective Laser Meltingmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective laser melting (SLM) is one of the most widely used additive manufacturing (AM) technologies for metallic materials [1]. With continuous improvements in SLM technology, many alloys, including Ti alloys [2], Al alloys [3], nickel-based superalloys [4], and certain steels, can be successfully processed using SLM, leading to high densities and favorable mechanical properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, these properties depend on the microstructure. Due to the fact that during additive manufacturing the selectively melted material rapidly cools down and thereby solidifies, the resulting microstructure as well as subsequent heat treatments are of particular importance to precipitate the strength-enhancing phases in the matrix and thus to achieve conventional mechanical properties of wrought and cast forms [4][5][6][7][8]. Specimens built by selective laser melting (SLM) typically show anisotropic mechanical properties, a fact which has to be taken into account when producing components by SLM [6,7].…”
Section: Introductionmentioning
confidence: 99%